2022
DOI: 10.1021/acs.jced.1c00794
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor–Liquid Equilibrium (PTxy) Measurements and Modeling of Propan-2-ol +n-Octane/n-Decane in the Range ofT= 313.2–353.2 K

Abstract: Vapor−liquid equilibrium measurements (P−T−x−y) are presented for propan-2-ol + n-octane/n-decane mixtures at three temperatures (T = 313.2, 333.2, and 353.2 K) and sub-atmospheric pressures, which were determined by the dynamic method in a recirculating still. The systems exhibit large relative volatilities, with azeotropic behavior observed for the propan-2-ol + n-octane system at all three measured temperatures. The experimental data were modeled using the γ−Φ regression formulation with the non-random two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…It can be observed that the azeotrope composition shifts toward the propanol-rich region with increasing temperature for both systems. Similar behavior was observed in recent previous work for the system propan-2-ol (1) + n -octane (2) …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It can be observed that the azeotrope composition shifts toward the propanol-rich region with increasing temperature for both systems. Similar behavior was observed in recent previous work for the system propan-2-ol (1) + n -octane (2) …”
Section: Resultssupporting
confidence: 90%
“…The nonideality of the systems is again indicated by the significant ratios between γ 1 ∞ and γ 2 ∞ at each temperature. This behavior is typical of alcohol–nonpolar hydrocarbon systems. , …”
Section: Resultsmentioning
confidence: 77%
“…The UNIQUAC model has been widely used in vapor–liquid equilibrium, liquid–liquid equilibrium, and solid–liquid equilibrium . This work adopts the modified UNIQUAC to calculate the solubility data .…”
Section: Solid–liquid Equilibrium Modelsmentioning
confidence: 99%